Dove Fields in Florida - William M. Giuliano; James F. Selph; Kurt Hodges; Nick Wiley (EDIS, 2007)
WEC-225, an 8-page illustrated fact sheet by William M. Giuliano, James F. Selph, Kurt Hodges, and Nick Wiley, describes how to use dove fields as a dove management tool within the guidelines barring hunting over a baited field. It discusses timing, location, size and number of dove fields, what to plant, planting, fertilization and liming, management, economics, and relevant laws. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, August 2007.